Clinical biochemical determinations in the Mangalarga-Paulista horse: reference values. - Novelli, E. L. [UNESP]; Rodrigues, N. L. [UNESP]; Chiacchio, S. B. [UNESP] (My University, 1993)
Biochemical values are widely related with environmental agents, sex and age, and are used in disease diagnosis. Numerous reports have been published on the biochemical parameters of different breeds of horses. However, there is a paucity of information concerning Cu-Zn superoxide dismutase (SOD), ceruloplasmin, copper and zinc determinations in the serum. Blood samples from a total of 60 horses of the Mangalarga-Paulista breed, representing three age groups (0 to 4 months old, 6 to 18 months old and adult) were examined. Male horses have a higher mean value of SOD, ceruloplasmin and copper than do females. No significant sex-related difference was observed in serum zinc content of weaned and adult horses. SOD activity was significantly higher in adult animals. Since SOD has a protective effect against superoxide free radical toxicity and possesses anti-inflammatory activity, it is reasonable to assume that the increased activity of this enzyme may be due to an adaptation mechanism which protects the adult animal against oxygen toxicity.